Form to Behaviour: Rethinking Group Form - Smolik, Andrei (Curtin University, 2021)
This thesis investigates form-generating processes in architecture using creative computing, digital fabrication and process design by exploring a series of creative small-scale built prototypes. The aim of this research is to develop understanding and explore novel methods and techniques for the development and fabrication of the built environment based on Group Form principles- compositional approach originally developed by Fumihiko Maki and representative of natural, spontaneous, large-scale systems and modular assemblies.